The new Husserl : a critical reader - Welton, Donn (Studies in Continental thought., 2003)
The recent first-time publication of works from Edmund Husserl's later years, especially his Freiburg period, combined with new studies of his method and theories, has stimulated a remarkable shift in perceptions of the scope and significance of Husserl's transcendental phenomenology. Informed by a deep reading of not just the works published during Husserl's lifetime but also the countless lectures and manuscripts he wrote in his later years, the essays in The New Husserl provide an alternative approach to Husserl by examining his work and his method as a whole and by probing issues, old and.